Analysis of Factors Influencing Green Growth in ASEAN Countries - Aldanny, Talitha Devina Zafirah; Nikensari, Sri Indah; Pratama, Aditya (International Journal of Applied Research and Sustainable Sciences, 2024)
Climate change is becoming an increasingly extreme challenge faced globally. As a result, green growth is built on the principle of sustainable economic expansion, rather than economic development based on excessive exploitation of natural resources and the environment. The purpose of this research is to examine the impact of renewable energy, green trade, and green financing on green growth in ASEAN countries. This research uses a quantitative approach with secondary data which is analyzed using the multiple linear regression method, and hypothesis testing is carried out simultaneously and partially using E-Views 12. The results of the research show that renewable energy, green trade, and green financing have a partial and simultaneous effect on green growth.